(untitled) (Medical Forum Monthly, 2026)
Due to the increase in caesarean sections worldwide, caesarean scar defects (CSD), also referred to as niches or isthmoceles, are becoming an increasingly more recognized complication. CSD can create long-term gynecological and reproductive complications. This review was conducted at Zulekha Hospital Sharjah United Arab Emirates from October 2025 till December 2025. This review included 65 studies conducted between the years 2000 and 2025 that examined imaging findings and clinical outcomes in relation to CSD. Transvaginal ultrasound (TVS) was the primary diagnostic method used, occasionally in conjunction with saline infusion sonohysterography (SIS) and three-dimensional (3D) ultrasound, as the 3D viewing angle permitted better accuracy of the diagnosis. There arecommon associated imaging findings such as niche depth was > 2mm and residual myometrium thickness (RMT) of < 3mm. CSD is also associated with secondary infertility in 28% - 40% of cases due to chronic inflammation with a likely impaired endometrial receptivity period. Obstetrical risks with CSD include uterine rupture, caesarean scar ectopic pregnancy, and placenta accreta spectrum when the RMT is < 2.5 mm. Although CSD is clinically significant in the caesarean population, there is still much inconsistency with the imaging diagnostic methods and management. There is a necessity for and consensus on the diagnostic criteria and further prospective research to establish the best possible management in clinical practice to improve reproductive outcomes for affected women.